Solvent-free Synthesis of Nitriles from Aldehydes Catalyzed by KF/Al2O3, Montmorillonite KSF and K10 - Li-Jun Li; Ying-Xia Song; Yan-Su Gao; Yan-Feng Li; Jian-Feng Zhang (E-Journal of Chemistry)
Multistep and one-pot conversion of aldehydes to nitriles were carried out conveniently with out solvent using KF/Al2O3, montmorillonite KSF and K10 as catalyst, under microwave irradiation. The reactions are completed within 6-8 min to give satisfactory yields. KF/Al2O3 was more effective catalyst both in multistep procedure and one-pot reaction.